A study of maintenance management of cleaning work at airport, office and commercial building in Kuala Lumpur / Nur Aizah Mohd. Naim - Mohd. Naim, Nur Aizah (2006)
Cleanliness has become a vital aspect in everybody's daily lives. The point is stressed in places with easy access to everyone such as shopping malls, airports, offices as well as hospitals. Scheduled and professional management form foundations to determine cleanliness levels in terms of all stages of cleaning work. Good maintenance management help ensure reduction in maintenance cost. Contractors must have their own daily, weekly or monthly schedule. They also need to prepare a budget of cleaning work like the worker's salary, equipment and detergent. Besides cleaning management, the techniques of cleaning must be accurate to measure cleanliness of the areas. The selection of equipment must be suitable for the job which includes internal and external areas of he building. Every element and place has specific technique of cleaning needs such as sweeping, wiping, mopping, buffing, water jetting and shampooing which require different techniques and applications. Therefore, seeing to it that cleaners need to be well trained to do their work, professional people who are aware of this issue have set up businesses, particularly training centers for cleaners, in this industry. The centre provides professional training for cleaners by their cleaning experts, hoping that the cleaners will implement the methods and techniques taught to them to maintain and clean buildings.